Pengelolaan Sumber Daya Air Berbasis Kearifan Lokal Sebagai Modal Untuk Pembangunan Berkelanjutan - Annisa Weningtyas; Endang Widuri (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2022)
Through local wisdom, indigenous peoples in Indonesia could survive the various water resource crises they face. This study aims to investigate the relationship between local wisdom and sustainable water resource management, as well as challenges to the existence of the local wisdom in managing water resources. This study implements normative legal research method, with a normative juridical approach. Data are collected from Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) and Law Number 17 of 2019 concerning Water Resources. The data are analyzed in a qualitative juridical manner. The results of the study conclude that UUPPLH and customary law have the same goal in providing protection for environmental management. Environmental issues should be addressed integrally, comprehensively, and holistically, so that technical aspects of operations, regulations, institutions, financing, and community participation are needed. In addition, preventive efforts are carried out through regional regulations as an elaboration and explanation of statutory regulations by taking into account the characteristics of each region; while repressive efforts in the context of enforcing environmental law require serious efforts by involving all law enforcement officers.